Identification of RPS14 as a 5q- syndrome gene by RNA interference screen - Ebert, Benjamin L. (2008)
Somatic chromosomal deletions in cancer are thought to indicate the location of tumor suppressor genes, whereby complete loss of gene function occurs through biallelic deletion, point mutation, or epigenetic silencing, thus fulfilling Knudson's two-hit hypothesis.(1) In many recurrent deletions, however, such biallelic inactivation has not been found. One prominent example is the 5q- syndrome, a subtype of myelodysplastic syndrome (MDS) characterized by a defect in erythroid differentiation.(2) Here, we describe an RNA interference (RNAi)-based approach to discovery of the 5q- disease gene. We find that partial loss of function of the ribosomal protein RPS14 phenocopies the disease in normal hematopoietic progenitor cells, and moreover that forced expression of RPS14 rescues the disease phenotype in patient-derived bone marrow cells. In addition, we identified a block in the processing of pre-rRNA in RPS14 deficient cells that is highly analogous to the functional defect in Diamond Blackfan Anemia, linking the molecular pathophysiology of the 5q- syndrome to a congenital bone marrow failure syndrome. These results indicate that the 5q- syndrome is caused by a defect in ribosomal protein function, and suggests that RNAi screening is an effective strategy for identifying causal haploinsufficiency disease genes.